Giant anisotropic photonics in the 1D van der Waals semiconductor fibrous red phosphorus - Luojun Du (Nature Portfolio, 2021)
One-dimensional van der Waals (1D vdW) materials derive interesting behaviour from dimensional confinement. Here the authors study a 1D vdW semiconductor, fibrous red phosphorous, and observe exceptional optical properties of large optical anisotropy and high photoluminescence.